Broadband penetration and economic growth: Do policies matter?. Issue 5 (August 2017) - Ghosh, Saibal
Highlights: Employs country-level data to examine the impact of broadband policies on broadband penetration. Also explores the impact of broadband penetration on economic growth and possible drivers. Broadband policies affect fixed broadband, whereas 3G services impact mobile broadband. There exists differential impact of broadband and 3G/4G services across countries. Broadband penetration raises growth, only when considered in tandem with growth drivers. Abstract: Although a significant body of literature has examined the interlinkage between broadband penetration and economic growth, the linkage between broadband policies and broadband penetration has been less studied in the literature. In addition, the role of 3G/4G services has also received limited attention. To address this issue, we combine the staggered timing of the implementation of broadband and 3G/4G services across countries and examine its impact on broadband penetration. Relatedly, we also examine the impact of broadband penetration on economic growth and the possible growth drivers. We find that while broadband policies improve fixed broadband penetration, 3G/4G services improve mobile broadband penetration; the magnitude of the latter being nearly three-times that of the former. Besides, we also uncover a positive effect of broadband penetration on economic growth, primarily working through a reduction in broadband prices and well as greater innovation and entrepreneurial activity.